Apostillas latinas - Gil, Juan (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
Conjectures to Lucr. 3. 836 (fueit instead of fuere), two metrical inscriptions (one of Coulogne [genitor nato instead of seni Tornato] and other of Spain [Feste la- instead of Festela]), Per. Eg. 24, 1 (partier instead of praeter) and a parallel (Altercatio Hadriani cum Epicteto) to the answer Quid est pauper (Petr. 48, 5) as a rhetorical school exercise.